The unfinished cycling city: embedding age-inclusion in urban cycling futures - Wilbert den Hoed (Urban, Planning and Transport Research)
In places with low overall cycling levels, the uptake by people of older ages tends to be especially marginal. This study observes that current cycling promotion in low-cycling cities does not change this tendency and argues that the ageing of urban populations increasingly requires action to address this gap. In response, it aims to understand the cycling trajectories of older adults who cycle or aim to take up cycling. The analysis focuses on their long-term mobility biographies, reporting from qualitative and mobile research methods applied in the city of Barcelona. This paper makes insightful how later life cycling is conditioned by interactions with the urban and social environment, but also how it carries essential qualities for positive ageing. The findings indicate that cycling currently relies on intrinsic mobile capacities that make it exclusive, less achievable as everyday transport mode, and less likely to endure over the lifecourse. The paper concludes that aspiring cycling cities should pay special attention to populations with less cycling representation and makes the case to advance age-friendliness in research and urban policies that wish to build-in and maintain cycling mobility across a wider demographic.